Can the ferroelectric soft mode trigger an antiferromagnetic phase transition?. Issue 6 (June 2023) - Maia, André; Kadlec, Christelle; Savinov, Maxim; Vilarinho, Rui; Moreira, Joaquim Agostinho; Bovtun, Viktor; Kempa, Martin; Míšek, Martin; Kaštil, Jiří; Prokhorov, Andriy; Jan Maňák,; Belik, Alexei A.; et al.
Abstract: Type-II multiferroics, where spin interactions induce a ferroelectric polarization, are interesting for new device functionalities due to large magnetoelectric coupling. We report on a new type of multiferroicity in the quadruple-perovskite BiMn3 Cr4 O12, where an antiferromagnetic phase is induced by the structural change at the ferroelectric phase transition. The displacive nature of the ferroelectric phase transition at 125 K, with a crossover to an order-disorder mechanism, is evidenced by a polar soft phonon in the THz range and a central mode. Dielectric and pyroelectric studies show that the ferroelectric critical temperature corresponds to the previously reported Néel temperature of the Cr 3+ spins. An increase in ferroelectric polarization is observed below 48 K, coinciding with the Néel temperature of the Mn 3+ spins. This increase in polarization is attributed to an enhanced magnetoelectric coupling, as no change in the crystal symmetry below 48 K is detected from infrared and Raman spectra.